In vitro antibacterial effects of antilipopolysaccharide DNA aptamer-C1qrs complexes - Bruno, J G; Carrillo, M P; Phillips, T (Folia microbiologica, 2008)
DNA aptamers were developed against lipopolysaccharide (LPS) from E. coli O111:B4 and shown to bind both LPS and E. coli by a colorimetric enzyme-based microplate assay. The polyclonal aptamers were coupled to human C1qrs protein either directly using a bifunctional linker or indirectly using biotinylated aptamers and a streptavidin-C1qrs complex. Both systems significantly reduced colony counts when applied to E. coli O111:B4 and K12 strains across a series of 10x dilutions of the bacteria in the presence of human serum; it was diluted 1: 10(3) in order to avoid significant bacterial lysis by the competing alternate pathway of complement activation. A number of candidate DNA aptamer sequences were cloned and sequenced from the anti-LPS aptamer library for future screening of antibacterial or "antibiotic" potential and to aid in eventual development of an alternative therapy for antibiotic-resistant bacterial infections.
Keywords: Complement C1; SELEX Aptamer Technique; aptamerová technika SELEX; sekvence nukleotidů; Lipopolysaccharides; infekce vyvolané Escherichia coli; lipopolysacharidy; antibakteriální látky; molekulární sekvence - údaje; aptamery nukleotidové; Escherichia coli Infections; Escherichia coli; lidé; Anti-Bacterial Agents; Humans; Aptamers, Nucleotide; Molecular Sequence Data; Base Sequence; komplement C1